Xenophobia and medicine (profession of a doctor): can the two coexist in the 21st century? - Basaran, Cem Hakan; Sayligil, Omur (Acta Bioethica, 2022)
This study was conducted to reveal how physicians view the access of refugees, who have difficulties in accessing health services and who may experience various health rights violations, to health services and to discuss the case in terms of medical ethics and deontology. Xenophobia, which is one of the main causes of discrimination in health, needs to be evaluated. In this context, quantitative research methods were used to measure the xenophobia levels of physicians working in Eskişehir province. Stratified sampling method was used to evaluate the views of the physicians. The study data were collected through the Xenophobia Scale developed by Kees Van Der Veer et al. and a questionnaire created by the researchers. The age distribution of the physicians in the study was 38,069±10,337. The distribution of the scores obtained from the xenophobia scale was found to be high (56.20±11.54). Of the physicians in the study, 34.3% stated that they would not want to provide health services for refugees if they were given the right to choose. They mainly thought that health services should not be provided free of charge for refugees and should be provided in separate places, refugees affected the access of the citizens of the Turkish Republic to health services negatively, the number of children should be limited, refugees would increase violence in health and public health problems, and that there should be an interpreter in health institutions. “Refugees do not deserve discrimination in health services” in terms of medical ethics. “Physicians should reach a common consensus against all kinds of discrimination while carrying out their profession.” When xenophobia shows its effect in the field of health, it turns into a phenomenon that damages human dignity, causes all kinds of inequality, and moves medicine away from its deontology.